ANALISIS PROGRAM MARKET DAY TERHADAP PENANAMAN NILAI-NILAI KEWIRAUSAHAAN DI SD AISYIYAH KUNINGAN - Indra Lesmana; Neng Lia Yulianengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
As time goes by, the function of education is not only to produce many graduates, but must be able to produce quality graduates so that students have the abilities and skills in accordance with the needs of the times, especially in the field of entrepreneurship. Even though at the elementary school level there is no requirement for a program or skills development in the field of entrepreneurship, the implementation of an effective entrepreneurship program is implemented at the elementary school level so that it can foster interest and form an entrepreneurial character that has the values ​​of honesty, discipline, responsibility and courage. taking risks and being creative from an early age. The aim of this research is to analyze the market day program, especially the entrepreneurial values ​​of class IV and V students at Aisyiyah Kuningan Elementary School with a sample of 5 people in that class, so the total sample is 10 people. The research method used is descriptive qualitative which explains the planning, implementation and evaluation of entrepreneurial values ​​at SD Aisyiyah Kuningan. The research techniques used in data collection are observation, interviews and documentation. The results of research and data analysis show that market day activities form entrepreneurial values ​​that are useful in the future, the values ​​that are formed are honest, disciplined, creative, brave to take risks, responsible, independent and have a leadership spirit.